Life Expectancy in Interwar Lithuania - Norkus, Zenonas (Socialinė teorija, empirija, politika ir praktika, 2017)
Life expectancy (e°x) is now considered one of the most valid and reliable measures of well-being, used for its cross-country and cross-time comparisons. The first complete life tables, which are necessary tools for the calculation of life expectancy, were published for Lithuania (for restricted use only) in 1963, covering the time period of 1958–1959. Since the 1970s, paleodemographic studies flourished in this country, conducted using osteological evidence. As a result, we now have better knowledge of the life expectancy in Lithuania during the middle iron (5–7th centuries AD) or late medieval ages than in during the 20th century (i.e., before 1958–1959). In fact, the only single calculation for this period was produced in 1966 by Antanas Merčaitis in his unpublished PhD dissertation, referring to the life expectancy of 1925–1926. As defined in his life tables, e°0 = 50, 25 years for the total population (males – 48.58; females – 51.89 years). This paper presents life tables for 1925 and 1932, constructed using a different method and disclosing an increasing life expectancy. In accordance with the present calculation, for the total population, e°0 = 48.72 years (males – 47.12; females – 50.27 years) in 1925. By 1932, e°0 = 52.07 for the total population (males – 50.43, females – 53.62 years). The paper closes with a comparison of life expectancies in Lithuania and other European countries during the interwar period.